Herbal Supplements and Cerebral Vasculopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A case of stroke attributed to a herbal energy drink containing sympathomimetic phenylpropanoid compounds is reported in a 21-year-old man treated at the University of Virginia, Charlottesville.